Rapid scan FTIR reveals propane (am)oxidation mechanisms over vanadium based catalysts. - Guerrero-Pérez, María Olga; McCue, Alan; Anderson, James (Elsevier, 2020)
Rapid scan FTIR coupled with Mass Spectrometry (MS) has been used to determine the role of spectroscopically observed species in the reaction media during propane dehydrogenation over a V/Al catalyst, and propane ammoxidation on a Sb-V-O sample. During the propane dehydrogenation reaction, it was shown that oxygenates are not formed during the first minutes and propylene is formed directly from propane via dehydrogenation on a V-O site. Oxygenates may form though secondary reactions due to further propylene oxidation. Propane dehydrogenation is the first step during the propane ammoxidation reaction. This is followed by the transformation of propylene into acrylonitrile, which is the rate limiting step. Rapid scan FTIR/MS is shown to be a useful technique for monitoring chemical reactions in order to identify or eliminate observed surface species as potential reaction intermediates. Understanding of the reaction mechanism is necessary in order to improve the chemical process design and the catalytic material.
Keywords: Catálisis; Espectroscopía de infrarrojo; Catalizadores de vanadio; FTIR; Catalysis